Structure‐function relationship between a natural cosmetic active ingredient and the olfactory receptor OR2AT4. (29th March 2019) - Verzeaux, L.; Richer, S.; Viguier, J.; Gofflo, S.; Boudier, D.; Aymard, E.; Closs, B.
Abstract: Objective: Although the olfactory receptor OR2AT4 was described as involved in epidermal renewal, there is no data about a cosmetic active ingredient activating this receptor. The aim of this research work was thus to identify a natural molecule binding to this receptor in order to stimulate keratinocyte migration. Methods: For this purpose, natural molecules were extracted from Cocos nucifera flour. Then, efficacy of this natural extract was evaluated on keratinocyte migration in vitro . Molecules of the Cocos nucifera flour extract were then identified by UPLC‐MS/MS. Molecular docking was finally conducted to investigate the potential interaction between identified molecules and the olfactory receptor OR2AT4. Results: The Cocos nucifera flour extract significantly increased keratinocyte migration and results demonstrated that this effect was mediated by the olfactory receptor OR2AT4. Metabolomic analysis revealed two molecules, nonioside D and butyl 4‐O‐alpha‐D‐glucopyranosyl‐beta‐D‐glucopyranoside, as significantly present in the Cocos nucifera flour extract compared to both Cocos nucifera oil and water. Finally, molecular docking revealed that butyl 4‐O‐alpha‐D‐glucopyranosyl‐beta‐D‐glucopyranoside could interact with the extracellular domain 2 of the OR2AT4. Conclusion: This study highlighted for the first time a natural molecule, extracted from Cocos nucifera flour, able to interact with the olfactory receptor OR2AT4 and promote the keratinocyte migration and thus the epithelialization.